History repeats? The rise of the new middle classes in the developing world - Mark Furness; Imme Scholz; Alejandro Guarín (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The hundreds of millions of people in Asia, Latin America and Africa whose incomes have increased over the last decade or so have been called the “new middle classes” of the developing world. This group is getting bigger. Their unprecedented size — likely to reach the billions by mid-century — means that these new middle classes will play an important role in their countries and beyond. If we define the middle classes as those who spend between US 10 and 100 (purchasing power parity, PPP) per day, by some projections this group will grow by more than one billion people in Asia alone in the next decade. The new middle classes will dwarf the “old” ones soon, shifting the centre of gravity of world consumption. In the West, the middle classes are seen as a huge part of the success story of the post-war years. They are considered fundamental for sustained economic growth, democracy and good political institutions. If this happens in developing countries, then it will be good news. But will it? A simple replay of history is unlikely. We do not know how society will change as incomes grow for millions of people in the developing world. The new middle classes could become forces for political, economic and social change both domestically and globally. But the opposite can also happen: once well established, they could act conservatively to protect their own positions and prevent further social change. This uncertainty presents a diverse set of challenges for development policy. First, people tend to use up more natural resources as they get richer. Reducing the environmental footprint of consumption must therefore be a global concern. Second, the growth of middle classes will not necessarily foster greater social inclusion. Development policy needs to prioritise reducing inequality as well as promoting growth. Third, rising incomes will not automatically lead to Western- style democracy. Open political systems should be encouraged regardless of the outcomes of political processes. Fourth, improved global governance is not a given. International cooperation among countries with larger and more assertive middle classes may become more difficult and complex.
Keywords: 330; Armut und Ungleichheit; Governance; Umwelt; Ökosysteme und Ressourcen